Implementations of Need based Approach to Credit Portfolio Management of Scheduled Commercial Banks in India (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
After the 2007-2008 global financial crises, the credit portfolio management function has become the most important function of banks and financial institutions. The third stage of the Basel Agreement, Basel III, was formulated after the crisis. It aims to strengthen banks' capital requirements by increasing bank liquidity and reducing bank leverage, and encourage banks to measure the credit risk of bank investment portfolios. The Basel Committee also raised the issue of applying the risk weights used in the capital adequacy framework to determine risky asset exposure to determine credit risk. (Morris,2001). The main purpose of this article is to analyze the credit implementation of the commercial banking sector and the implementation of demand-based credit management methods. This research analyzes the concentration of loans and the total amount of bad debts by sector and product, and studies the concentration of banks in credit portfolio management. This research also aims to provide some suggestions for overcoming the problems associated with credit portfolios.